Stimulant Therapy in Acute Traumatic Brain Injury: Prescribing Patterns and Adverse Event Rates at 2 Level 1 Trauma Centers. (November 2020) - Barra, Megan E.; Izzy, Saef; Sarro-Schwartz, Aliyah; Hirschberg, Ronald E.; Mazwi, Nicole; Edlow, Brian L.
Background/Objective: Pharmacological stimulant therapies are routinely administered to promote recovery in patients with subacute and chronic disorders of consciousness (DoC). However, utilization rates and adverse drug event (ADE) rates of stimulant therapies in patients with acute DoC are unknown. We aimed to determine the frequency of stimulant use and associated ADEs in intensive care unit (ICU) patients with acute DoC caused by traumatic brain injury (TBI). Methods: We retrospectively identified patients with TBI admitted to the ICU at 2 level 1 trauma centers between 2015 and 2018. Patients were included if they were stimulant naive at baseline and received amantadine, methylphenidate, or modafinil during ICU admission. Stimulant dose reduction or discontinuation during ICU admission was considered a surrogate marker of an ADE. Targeted chart review was performed to identify reasons for dose reduction or discontinuation. Results: Forty-eight of 608 patients with TBI received pharmacological stimulant therapy (7.9%) during the study period. Most patients were diagnosed with severe TBI at presentation (60.4%), although stimulants were also administered to patients with moderate (14.6%) and mild (25.0%) TBI. The median time of stimulant initiation was 11 days post-injury (range: 2-28 days). Median Glasgow Coma Scale score at the time of stimulant initiation was 9 (range: 4-15). Amantadine was the most commonly prescribed stimulant (85.4%) followed by modafinil (14.6%). Seven (14.6%) patients required stimulant dose reduction or discontinuation during ICU admission. The most common ADE resulting in therapy modification was delirium/agitation (n = 2), followed by insomnia (n = 1), anxiety (n = 1), and rash (n = 1); the reason for therapy modification was undocumented in 2 patients. Conclusions: Pharmacological stimulant therapy is infrequently prescribed but well tolerated in ICU patients with acute TBI at level 1 trauma centers. These retrospective observations provide the basis for prospective studies to evaluate the safety, optimal dose range, and efficacy of stimulant therapies in this population.